Character-Based Holistic Education Management at PAUD An-Nahl - Anton Anton; Alexy Bolry (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Management that is not good will tends to fail to change the character of students. The purpose of this article was written to find out good management to change character. Character-based holistic education management at PAUD An-Nahl in Payakumbuh District, Payakubuh City can provide information about good management for changing character. This research uses a qualitative descriptive approach with a case study method. In-depth interviews and documentation are the techniques used for data collection. From in-depth interviews and documentation, it was found that the results of research conducted at PAUD An-Nahl in Payakumbuh District that the application of character-based holistic education at An-Nahl PAUD in Payakumbuh District has succeeded in shaping students into children with good character